Early triadic interactions in the first year of life: a systematic review on object-mediated shared encounters - Mendoza-García, Ana; Moreno-Núñez, Ana (Frontiers in Psychology, 2023)
Infants' early interactions with adults and everyday objects are key to socio-communicative development, but their emergence and development are still under debate. Aiming at describing the diversity of theoretical and methodological approaches on triadicity during the first year of life, we conducted a systematic and qualitative review of recent literature. Following PRISMA 2020 guidelines, we explored the scientific production of recent decades on triadic interactions up to 12 months of age. We initially screened 1943 items from which we obtained a final sample of 51 publications. Studies are usually conducted in laboratory settings, while ecological research is becoming increasingly common, especially in home settings. According to a thematic analysis of the data, we discussed the different perspectives on the origin and conceptualization of triadic interactions, and how they contribute to structuring and facilitating other developmental phenomena, such as the children's communicative gestures and uses of objects. Prior to the origin of intentional communication, adults facilitate early forms of triadicity based on fostering opportunities for infants' communication and engagement with both adults and materiality. However, there is a need for further research that explore the potential of early triadic interactions for parenting and early childhood education practices.Eliminado: From this point of view, triadic interactions exist from 85 the beginning of life, as adults and infants communicate about-and 86 through-the material world on a daily basis (Rodríguez, 2012).